2019
DOI: 10.1007/s12668-019-00620-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Release Kinetics and Mechanisms of Curcumin and Curcumin-β-Cyclodextrin Inclusion Complex Incorporated in Electrospun Almond Gum/PVA Nanofibers in Simulated Saliva and Simulated Gastrointestinal Conditions

Abstract: Curcumin and curcumin-β-cyclodextrin (CD) inclusion complex were successfully encapsulated in almond gum/polyvinyl alcohol (PVA) nanofibers using electrospinning procedure. The release mechanisms and kinetics of encapsulated curcumin and curcumin-βCD inclusion complex were evaluated in simulated gastrointestinal and simulated saliva conditions. The release data were fitted to zero order, Kopcha, Korsmeyer-Peppas, and Higuchi models to evaluate release mechanisms and kinetics. The controlled release of curcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 43 publications
4
39
0
Order By: Relevance
“…[81] As the effectiveness of drug release has dependence with its release mechanism that can be including can be a mechanism of swelling, diffusion, desorption, and/or degradation of the matrix [6,13] the release mechanism of P 4 -loaded CA nanofibers was also evaluated. As the Higuchi and Zero-order kinetic models are commonly used to describe drug release profiles, [82,83] including to study the release mechanism in polymer nanofibers mats structures, [84,85] these models were chosen to analyze the data in the first release stage, that is, the burst release. Comparing the results presented in Figure 7A,B it was concluded that Higuchi kinetic model was the model that best suits the behavior of the samples with 4, 6, 8, and 10% w/w P 4 samples.…”
Section: P 4 -Loaded Ca Nanofibers Release Behaviormentioning
confidence: 99%
“…[81] As the effectiveness of drug release has dependence with its release mechanism that can be including can be a mechanism of swelling, diffusion, desorption, and/or degradation of the matrix [6,13] the release mechanism of P 4 -loaded CA nanofibers was also evaluated. As the Higuchi and Zero-order kinetic models are commonly used to describe drug release profiles, [82,83] including to study the release mechanism in polymer nanofibers mats structures, [84,85] these models were chosen to analyze the data in the first release stage, that is, the burst release. Comparing the results presented in Figure 7A,B it was concluded that Higuchi kinetic model was the model that best suits the behavior of the samples with 4, 6, 8, and 10% w/w P 4 samples.…”
Section: P 4 -Loaded Ca Nanofibers Release Behaviormentioning
confidence: 99%
“…Hence, Cur-CSCaCO3NP release mechanism obeyed the Higuchi model release manner. The Higuchi model of drug release from of curcumin from other nanoparticles were reported earlier by previous studies [38,39,70,71].…”
Section: Ft-irmentioning
confidence: 86%
“…The formation of IC leads to considerable improvements in the properties of the guest molecules such as protection for evaporation, degradation, oxidation, enhancing solubility, chemical stability, and controlling the release rate. Curcumin-β-cyclodextrin IC was successfully encapsulated in electrospun almond gum/PVA nanofibers and tested in simulated gastrointestinal and simulated saliva medium, in both media the release was governed by diffusion mechanism, higher solubility of curcumin after its complexion with CD lead to higher release in simulated saliva conditions [66]. In another work, α-tocopherol (vitamin E) was complexed with β-Cyclodextrin and then encapsulated in Polycaprolactone (PCL) and compared with electrospun PCL -TC without CD-IC.…”
Section: Electrospun Nanoparticles/polymers Systems For Ddsmentioning
confidence: 99%
“…All mechanisms can act at the same time and significantly influence the kinetics without a model capable to describe all kinds of mechanisms in DDS. Despite this, several models have been proposed to describe diffusion by solving Fick's second law of diffusion and non-Fickian behavior associated with the swelling of polymers and solvents uptakes [66,76]. A common approach is to consider time and spatial dependent coefficient diffusion that takes into account the change in solvent diffusivity across the swelling front.…”
Section: Kinetics and Mechanismsmentioning
confidence: 99%